DISTRACTIONS. - Holzman, Michael (Sun (Chapel Hill NC), 2026)
The article focuses on the author's personal experience with learning challenges related to understanding main ideas in texts during their school years, and how this evolved into a strength as a rabbi. The author describes struggling with traditional academic assessments that emphasized singular interpretations, contrasting this with their current approach of embracing multiple ideas and connections across diverse texts, including the Torah, Talmud, and modern stories. They highlight success in supporting students, particularly boys labeled as inattentive, by encouraging creative and open-ended thinking, which leads to meaningful engagement. The author reframes what is often seen as distraction as "superawareness," a heightened sensitivity to details that fosters deeper appreciation and understanding.